Innate Immune Recognition of Francisella Tularensis: Activation of Type-I Interferons and the Inflammasome - Jones, Jonathan W.; Broz, Petr; Monack, Denise M. (Frontiers in Microbiology, 2011)
Francisella tularensis is an intracellular pathogen that can cause severe disease in a wide range of mammalian hosts. Primarily residing in host macrophages, F. tularensis escapes phagosomal degradation, and replicates in the macrophage cytosol. The macrophage uses a series of pattern recognition receptors to detect conserved microbial molecules from invading pathogens, and initiates an appropriate host response. In the cytosol, F. tularensis is recognized by the inflammasome, a multiprotein complex responsible for the activation of the cysteine protease caspase-1. Caspase-1 activation leads to processing and release of proinflammatory cytokines and host cell death. Here we review recent work on the molecular mechanisms of inflammasome activation by F. tularensis, and its consequences both in vitro and in vivo. Finally, we discuss the coordination between the inflammasome and other cytosolic host responses, and the evidence for F. tularensis virulence factors that suppress inflammasome activation.